PENGARUH ARANG SEKAM PADI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KACANG HIJAU PADA TANAH PODSOLIK MERAH KUNING - Deky Wahyudi; Rini Susana; Dwi Zulfita (Fakultas Pertanian, Universitas Janabadra, 2023)
Increasing green bean production in West Kalimantan can be done through the utilization of marginal red yellow podzolic soils. Constraints of red yellow podzolic soil as a planting medium are having lumpy soil structure, low permeability, poor aeration and drainage, low water holding ability can be improved by adding rice husk charcoal which has the advantage of improving porosity and aeration as well as a binder of nutrients so that they are not easily washed out. This study aims to determine the best dose of husk charcoal for the growth and yield of mung beans on red yellow podzolic red yellow podzolic. The research was carried out in the experimental field of the Faculty of Agriculture, Tanjungpura University, Pontianak. This study used a Completely Randomized Design (CRD) which consisted of 6 treatment levels and 4 replications, each replication consisting of 3 samples so that there were 72 plants. The treatment consisted of a0 = without rice husk, a1 = 5 tonnes/ha , a2 = 10 tonnes/ha, a3 = 15 tonnes/ha, a4 = 20 tonnes/ha and a5 = 25 tonnes/ha. The variables observed in this study were plant height, root volume, plant dry weight, number of pods per plant, seed weight per plant, and weight of 100 seeds. The results showed that the application of rice husk charcoal at a dose of 25 tons/ha gave the best growth and yield of green bean on red yellow podzolic soil.INTISARI Peningkatan produksi kacang hijau di Kalimantan Barat dapat dilakukan melalui pemanfaatan tanah marginal Podsolik Merah Kuning (PMK). Kendala tanah PMK sebagai media tanam adalah memiliki struktur tanah gumpal, permeabilitas rendah, aerasi dan drainase buruk, kemampuan menahan air rendah dapat diperbaiki dengan pemberian arang sekam yang memiliki keunggulan memperbaiki porositas dan aerasi serta sebagai pengikat hara agar tidak mudah tercuci. Penelitian ini bertujuan untuk mengetahui dosis arang sekam yang terbaik bagi pertumbuhan dan hasil kacang hijau pada tanah PMK. Penelitian dilaksanakan di lahan percobaan Fakultas Pertanian Universitas Tanjungpura Pontianak. Penelitian menggunakan Rancangan Acak Lengkap yang terdiri dari 6 taraf perlakuan dan 4 ulangan, masing masing ulangan terdiri dari 3 sampel sehingga terdapat 72 tanaman. Perlakuan terdiri dari a0 = tanpa pemberian aramg sekam , a1 = 5 t/ha, a2 = 10 t/ha, a3 = 15 t/ha, a4 = 20 t/ha dan a5 = 25 t/ha. Variabel yang diamati adalah tinggi tanaman, volume akar, berat kering tanaman, jumlah polong per tanaman, berat biji per tanaman, dan berat 100 biji. Hasil penelitian menunjukkan pemberian arang sekam padi dengan dosis 25 ton/ha memberikan pertumbuhan dan hasil tanaman kacang hijau yang terbaik pada tanah Podsolik Merah Kuning.